Multimedia-based E-Puzzle Development to Improve Visual-Spatial Abilities and Early Childhood Religious Character - Wathoni, Hizbul; Kustiono, Kustiono; Ahmadi, Farid (Journal of Primary Education, 2021)
The using of E-Puzzle media-based multimedia will combine various types of media needed in the game. For example, with images, text, and other media, students will use it directly through the computer-integration, namely E-Puzzle application software based on Adobe Flash Professional CS6. This study aims to develop E-Puzzle mediabased multimedia to improve the visual-spatial abilities and religious character of early childhood. This study used R&D (research and development) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) and the research design uses pre-experimental design. The subjects in this study were 12 students of group B Raudhatul Athfal Tawang Rejosari and Raudhatul Athfal Terpadu Al-Qolam. Data collection techniques was used observation, interviews, questionnaires, and tests. The data analysis technique in this research is descriptive test and prerequisite test. The results showed that visual-spatial stimulation includes an increase in the ability to perceive image patterns and colors. Simultaneously, the religious character is about knowledge of moral values, moral feelings, and moral actions through prayer movement images in the form of puzzles as an integrated learning medium with Adobe Flash Professional CS6 applications. This development is effectively used to improve children's visual-spatial abilities and religious character aged 5-6 years. Based on the results of expert validation with a mean score of 69.33%, while the N-Gain score results of the experimental class of 77.00 are in the high category and N-Gain in the controllerclass is 44.06, which belongs to the moderate category. This research can be an innovation related to multimedia in early childhood education, especially for researchers, and can be a reference for future researchers.